Investigation of moisture distribution in Malaysian wood by neutron radiography [compact disc] - 259103 Yeong, Wai Woon (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Science (Health Physics)) - Universiti Teknologi Malaysia, 2004